2018
DOI: 10.1016/j.bja.2018.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of perioperative dexmedetomidine on postoperative delirium: systematic review and meta-analysis with trial sequential analysis of randomised controlled trials

Abstract: PROSPERO: CRD42017072380.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
145
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(156 citation statements)
references
References 38 publications
9
145
1
1
Order By: Relevance
“…However, the inclusion of clonidine and mivazerol in this study may have introduced some bias and hampered the interpretation of the effects of DEX. Another meta-analysis showed a lower prevalence of postoperative delirium in adult cardiac and noncardiac surgical patients who received DEX, but did not present data on mortality, duration of hospital stay, or other complications [63]. An additional meta-analysis did not reach a conclusion about the overall effects of perioperative DEX use on postoperative outcomes in surgical patients due to lack of evidence [64].…”
Section: Discussionmentioning
confidence: 99%
“…However, the inclusion of clonidine and mivazerol in this study may have introduced some bias and hampered the interpretation of the effects of DEX. Another meta-analysis showed a lower prevalence of postoperative delirium in adult cardiac and noncardiac surgical patients who received DEX, but did not present data on mortality, duration of hospital stay, or other complications [63]. An additional meta-analysis did not reach a conclusion about the overall effects of perioperative DEX use on postoperative outcomes in surgical patients due to lack of evidence [64].…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine (DEX) is an α 2 ‐adrenoceptor agonist that has sedative and analgesic effects, and has been widely used clinically as an adjuvant of anesthesia to provide analgesia and sedation in the preoperative and postoperative periods (Kamibayashi, 2000). These effects are useful for the prevention of postoperative delirium (Duan et al, 2018). Moreover, DEX protects organs in various injury models including ischemia (Dahmani et al, 2005; Engelhard et al, 2002; Eser et al, 2008; Goyagi et al, 2009; Zhu et al, 2013), inflammation (Vincent Degos et al, 2013), and traumatic injury (Schoeler et al, 2012), owing to its anti‐apoptotic effects (Engelhard et al, 2002), its ability to decrease caspase‐3 elevation (Dahmani et al, 2005; Eser et al, 2008), its effects on the phosphoinositide 3‐kinase (PI3K)/Akt and extracellular signal‐regulated kinase 1/2 (ERK1/2) pathways (Zhu et al, 2013) via the α 2A and imidazole 1 receptors (Ma et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…137,138 A subsequent systematic review and metaanalysis that examined the efficacy of perioperative dexmedetomidine on POD did a subgroup analysis on these three studies and found that perioperative administration of dexmedetomidine may decrease POD. 134 A recent review supported this, but found no evidence that dexmedetomidine reduced POCD. 140 Clonidine decreased delirium severity in a small thoracic surgery cohort in one study without changing its incidence.…”
Section: Preventionmentioning
confidence: 99%